Pengaruh Perbandingan Katalis ZSM-5 dengan Katalis Alumina terhadap Pembentukan Biofuel dengan Bahan Baku Minyak Jelantah - Paqih Purnama Alam; I Wayah Adithama Nugraha; Mukhtar Ghozali; Dian Ratna Suminar (Jurusan Teknik Kimia, Politeknik Negeri Bandung, 2021)
The average consumption rate of cooking oil in Indonesia on 2019 was 61 million litre. Because of that makes the waste cooking oil produces very high to. To prevent the consument littering the waste cooking oil, we can recycle it to be biofuel with many fraction such as biodiesel, biogasoline, and biokerosene. There are many ways to process the waste cooking oil to be, biofuel one of them is catalytic cracking. This study is induct by observe the biofuel that form from the catalytic cracking process with cooking oil as the base material using a hybrid catalyst ZSM-5/Alumina. The purpose of this study is to observe the influence of ZSM-5 and Alumina ratio as heterogenic catalyst and also the used of the catalyst frequently. The highest conversion of liquid product was produce with value 41,67% at alumina variation of 17,5%. The used of catalyst frequently will affect the decrease amount of liquid product that produce. The analysis of chemical properties using GC-MS obtained the amount of kerosene 29,917 %; gasoline 3,996 %; and diesel 10,1 %. The other product was carboxylics acids,alcohol, and unidentified compound. Keyword : Cooking oil, biofuel, ZSM-5, Alumina, catalytic cracking